Leaching Characteristics of Udipsamment Ameliored by Mineral Soil and Adhesive Polymer - Fibrianty Fibrianty; Eko Hanudin; Azwar Ma’as (UNIVERSITY OF LAMPUNG, 2022)
Udipsamment is characterized by sand fraction > 95%, loose, and very high leaching. This study aimed to determine the effect of mineral soil ameliorants and adhesive polymers on the character of nutrient leaching in Udipsamment. The leaching study in lysimeters used a completely randomized design with three replications. The treatments consist of bagasse (B), mineral soil included Inceptisol (I) and Vertisol (V), and adhesive polymers included tapioca 1% and 2% (T1 and T2), tapioca dregs 1% and 2 % (A1 and A2), Polyvinylalcohol 0.1% and 0.2% (P1 and P2). Combination of treatments are IB, VB, IBT1, IBT2, VBT1, VBT2, IBA1, IBA2, VBA1 , VBA2 , IBP1, I BP2, VBP1, and VBP2. Observations were made before and after leaching. The research showed that VBT2 increases moisture-holding capacity. Amelioration improved the ability of Udipsamment to hold nutrients, after leaching for six months, there was a decrease in organic C, total N, and available P compared to before leaching. Amelioration increased the soil CEC, even up to the sixth month leaching, the soil CEC showed a higher value than before leaching. The amount of clay fraction was relatively uniform between the surface and the bottom of the lysimeter, indicating that the adhesive polymer successfully bonding the clay-sand particles and prevented clay leaching.